2013
DOI: 10.1108/info-05-2013-0032
|View full text |Cite
|
Sign up to set email alerts
|

ICT policy and poverty reduction in Africa

Abstract: Purpose -The purpose of this paper is to understand how policymakers in different African countries negotiate the complex relationship between information and communication technologies (ICTs) and poverty reduction. The authors adopt a novel perspective on this problem by considering how the broader policy discourse and associated mechanisms tend to address (or neglect) the multiple dimensions of poverty.Design/methodology/approach -A textual analysis was conducted on selected ICT and poverty reduction policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 13 publications
(14 reference statements)
0
20
0
1
Order By: Relevance
“…In a general sense, economic development through ICT provisions is not automatically translated into higher levels of social progress, and the policies that promote growth through ICT have to be complemented with other policy measures to foster social inclusion (Osakwe & Moussa, 2017). One reason for this hard translation is that many ICT policy makers struggle to convert these nuanced concepts into practical policy interventions that should underpin development and betterment in the lives of the most disadvantaged (Diga et al, 2013). In many developing countries the government acts as the key facilitator of innovations; in Africa, governments have been connoted by a weak institutional relationship between public and private sector (Asheim, Coenen, Bugge, & Herstad, 2017;Biseswar et al, 2012).…”
Section: The Diffusion Of Innovation In Developing Countriesmentioning
confidence: 99%
See 3 more Smart Citations
“…In a general sense, economic development through ICT provisions is not automatically translated into higher levels of social progress, and the policies that promote growth through ICT have to be complemented with other policy measures to foster social inclusion (Osakwe & Moussa, 2017). One reason for this hard translation is that many ICT policy makers struggle to convert these nuanced concepts into practical policy interventions that should underpin development and betterment in the lives of the most disadvantaged (Diga et al, 2013). In many developing countries the government acts as the key facilitator of innovations; in Africa, governments have been connoted by a weak institutional relationship between public and private sector (Asheim, Coenen, Bugge, & Herstad, 2017;Biseswar et al, 2012).…”
Section: The Diffusion Of Innovation In Developing Countriesmentioning
confidence: 99%
“…Chen (2014) noted that part of these uncertainties are strongly related to the imbalances of technological advances especially in what refers to the creation of jobs and extensive use of capital-intensive technology. Yet, the literature on poverty and ICT in Africa suggested that key mechanism to support the adoption of innovations amid such uncertainties, lies in making ICT content, services, and infrastructure more accessible and suitable to low-literacy impoverished communities (Diga et al, 2013). Researchers, therefore, considered the demographic and socioeconomic profile of the people, such as income, gender, age, education, and so on, to make decisions to adopt technological innovations as long as these factors address their specific household needs (Tigabu, 2017).…”
Section: The Diffusion Of Innovation In Developing Countriesmentioning
confidence: 99%
See 2 more Smart Citations
“…For ICT's role in struggle with poverty see e.g. Weber, Kulkarni and Riggins (2012), Diga, Nwaiwu, and Plantinga (2013). For ICT's contribution to education domain, see e.g.…”
mentioning
confidence: 99%